Becoming Indigenous: the 'speculative turn' in anthropology and the (re)colonisation of indigeneity - Chandler, David; Reid, Julian (Postcolonial studies, 2020)
The Indigenous have become central to contemporary critical and governmental imaginaries as the West tries to cope with planetary crises imbricated in the legacies of modernity and settler colonialism. As such, Indigenous methods and practices are increasingly constructed as offering futural possibilities for 'becoming' rather than belonging to the archives of an underdeveloped past. Central to this transformation has been the speculative or ontological turn in anthropological discourse, which we argue has opened up new possibilities for a Western and colonial appropriation of indigeneity. This turn is the subject of this article and is critically engaged with to pursue a number of avenues which problematise this form of 'ontopolitical anthropology'. The reduction of Indigenous lives to the speculative 'other' of Western modernity inherently tends to reify or 'exoticise' Indigenous thought and practices or, as we state, to 'ontologize indigeneity'. This, we argue, is particularly problematic in the context where critical imaginaries of precarious 'life in the ruins' tend to affirm contemporary governmental approaches rather than challenge them. Ironically, rather than opening up alternative possibilities, these approaches reduce the reality of Indigenous struggles and sufferings to a mere foil for the speculative imaginaries of a privileged white Eurocentric academic elite.